We are the leaders we have been looking for - Glaude, Eddie S., Jr., 1968- (W.E.B. Du Bois lectures., 2024)
"Based on the Du Bois Lectures delivered at Harvard in 2011, We Are the Leaders We Have Been Looking For argues for the importance of self-cultivation in pursuit of justice as a critical feature of Black politics, what Eddie S. Glaude Jr. calls Black democratic perfectionism. Building on the political scientist Adolph Reed's work on 'Black custodial politics' Glaude critiques our impulse to outsource political needs to a professional class of politicians that purportedly represent us. Instead, he affirms the capacities of ordinary people to cultivate a better self and a better world by locating the prophetic and the heroic not in the pulpit but in the pew"--